DIFFUSION OF THE TECHNOLOGICAL INNOVATION e-SUS AB: ACCEPTANCE OR REJECTION? - Talita Ingrid Magalhães Silva; Ricardo Bezerra Cavalcante; Hugo Ricardo Moreira da Silva; Regina Consolação Santos; Eliete Albano de Azevedo Guimarães; Marta Macedo Kerr Pinheiro (Universidade Federal do Paraná, 2018)
Objective: analyze the diffusion of the technological innovation "e-SUS AB strategy" in a Family health team in the West of Minas Gerais. Method: single case study with a qualitative approach in the light of the Innovation Diffusion Theory and the Technology Acceptance Model. The data collection included an interview and direct observation of a team's daily work. The data were systemized in the software Atlas ti and analyzed through Content Analysis. Results:the innovation supports the care planning because it makes individualized data available and improves the daily work. Nevertheless, its diffusion has predominantly produced a work overload and other difficulties that limit its acceptance by the health professionals. Conclusion: the diffusion of the e-SUS AB strategy as a technological innovation has presented situations that strengthen its acceptance, but situations that can lead to its rejection were predominant.